If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (h * h) + h = 6 Multiply h * h (h2) + h = 6 h2 + h = 6 Reorder the terms: h + h2 = 6 Solving h + h2 = 6 Solving for variable 'h'. Reorder the terms: -6 + h + h2 = 6 + -6 Combine like terms: 6 + -6 = 0 -6 + h + h2 = 0 Factor a trinomial. (-3 + -1h)(2 + -1h) = 0Subproblem 1
Set the factor '(-3 + -1h)' equal to zero and attempt to solve: Simplifying -3 + -1h = 0 Solving -3 + -1h = 0 Move all terms containing h to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1h = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1h = 0 + 3 -1h = 0 + 3 Combine like terms: 0 + 3 = 3 -1h = 3 Divide each side by '-1'. h = -3 Simplifying h = -3Subproblem 2
Set the factor '(2 + -1h)' equal to zero and attempt to solve: Simplifying 2 + -1h = 0 Solving 2 + -1h = 0 Move all terms containing h to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1h = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1h = 0 + -2 -1h = 0 + -2 Combine like terms: 0 + -2 = -2 -1h = -2 Divide each side by '-1'. h = 2 Simplifying h = 2Solution
h = {-3, 2}
| 4Y-3=29 | | 2(h*h)+h=21 | | 6(h*h)+2h=28 | | 0=x^2-78x-1911 | | 2Y=128 | | Y-7=21 | | 5y+11=3(y+7) | | X+16=35 | | 7x+5=(2x+3)(4x+1) | | 2x^2+14x+54=0 | | x^2+14+54=0 | | 7x-x^2-15=0 | | 10(3k+1)=2(9+11) | | x+(x+1)=10 | | -x^2-2x+4=0 | | 4(x+2)-2=34 | | 107-6x=21x+23 | | 2n^2+n=0 | | 9(q-2)=3(9-12) | | 10-8x=125-43x | | 300-12x=400-17x | | 5(x-3)-2(x-3)-9=0 | | 3x+(x-1)+(3x+1)=56 | | -16(3-29)=432 | | 3x^4*x-10=0 | | (x-6)(3x-2)=(x-16)(2x+1) | | 2x-1=7-4x | | (2x+1)(x-16)=(3x-2)(x+3) | | 0.36p+0.26=3.36 | | 0.4(0.1x+.3)=-0.8 | | 2x^2-10x-3=0 | | (-5x/7)-8=-9 |